Expression of Exhaustion Markers on CD8+ T-Cell Patterns Predict Outcomes in Septic Patients Admitted to the ICU*. Issue 9 (22nd April 2021) - Guinault, Damien; Nicolau-Travers, Marie-Laure; Silva, Stein; Cointault, Olivier; Daniau, Barnabé; Del Bello, Arnaud; Peres, Michael; Rousset, David; Rieunier, Julie; Lavayssiere, Laurence; Nogier, Marie-Béatrice; Hourcastagnou, Edith; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : RATIONALE: There is an unmet need to improve the description of the state of T-cell exhaustion in patients with sepsis, its reproducibility and correlation with the outcomes before including immunotherapy (like recombinant interleukin-7 or immune checkpoint inhibitors) in the therapeutic armamentarium against sepsis. DESIGN: Observational prospective study. SETTING: Two ICUs in a teaching hospital (France). PATIENTS: Eighty patients with sepsis admitted to the ICU. INTERVENTIONS: Quantification of CD4 + and CD8 + T-cell exhaustion at days 1 and 3. Quantification of the exhaustion markers (programmed death [PD]-1, 2B4, and cluster of differentiation [CD] 160) on T cells, the number of CD4 + regulatory T cells (CD3 + CD4 + CD25 hi CD127Lo cells), and the phorbol myristate acetate/ionomycin/ionomycin-induced cytokines production (tumor necrosis factor-α, interleukin-2, and interferon-γ). MEASUREMENTS AND MAIN RESULTS: Using unsupervised clustering analysis, patients could be split in three clusters according to their dominant pattern expression of exhaustion markers on CD8 + T cells (i.e., 2B4 low PD-1 low CD160 low, 2B4 hi PD-1 hi CD160 low, and 2B4 hi PD-1 low CD160 hi ) regardless of their underlying morbidities. Only 2B4 hi PD-1 hi CD160 low CD8+ T cells had cytokine production defect, whereas 2B4 hi PD-1 low CD160 hi pattern correlated with cytokine overproduction. Patients with a predominant "highly activated" 2B4 hi PD-1 low CD160 hi pattern did not develop secondary bacterial infections. By multivariate analysis, Simplified Acute Physiology Score 2 gravity score at day 1 ( p = 0.003) and patterns of exhaustion markers on CD8 + T cells ( p = 0.03) were associated with the risk of death. Neither the level of CD4 + regulatory T cells nor the CD4 + exhaustion patterns were associated with the outcomes. CONCLUSIONS: Easy-to-use multicolor flow cytometry assessing 2B4, PD-1, and CD160 expression on CD8 + T cells at day 1 identifies septic patients with poor outcome and discriminates patient subsets in who immunomodulatory drugs should be tested.